Even more new species, additional records, and a revised key for Philothalpus Kraatz (Coleoptera: Staphylinidae: Staphylininae) - Chatzimanolis, Stylianos (Zootaxa, 2020)
Two species of Philothalpus Kraatz are described as new: P. anapodos n. sp. Chatzimanolis, from Madre de Dios, Peru and P. boreios n. sp. Chatzimanolis from El Salvador, Guatemala and Costa Rica. Additional distributional records are provided for P. asymmetros Chatzimanolis & Ashe, P. bilobus Chatzimanolis & Ashe, P. fervidus (Erichson), P. juanecoi Asenjo & Ribeiro-Costa, P. mundus (Sharp) and P. rugosus Chatzimanolis & Ashe. A revised identification key is provided that includes all species of Philothalpus.